2007
DOI: 10.1103/physrevlett.99.156101
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Quasicrystals of Decagonal Order in One-Component Monolayer Films

Abstract: By using Monte Carlo simulations we demonstrate that atomic monolayers formed on a crystalline surface may exhibit quasicrystalline decagonal order. It is shown that the stability of two-dimensional quasicrystals (QCs) is determined by the misfit between the adsorbate and the surface lattice and by the corrugation of the surface potential. QCs may be stable at the ground state or develop from the compressed commensurate c(2 x 2) structure, via the first-order phase transition at finite temperatures. The decago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In systems of patchy colloids the ordering preferred by the isotropic part of the potential (with only one length scale) competes with structures that possess the binding angles preferred by the patches. Competitions between different symmetries are known to lead to interesting new phenomena, like the formation of Archimedeantiling phases [33][34][35][36], rhombic phases [37], or new types of growth behavior [38,39]. Here we report on similar intermediate orderings of patchy colloids.…”
mentioning
confidence: 64%
“…In systems of patchy colloids the ordering preferred by the isotropic part of the potential (with only one length scale) competes with structures that possess the binding angles preferred by the patches. Competitions between different symmetries are known to lead to interesting new phenomena, like the formation of Archimedeantiling phases [33][34][35][36], rhombic phases [37], or new types of growth behavior [38,39]. Here we report on similar intermediate orderings of patchy colloids.…”
mentioning
confidence: 64%
“…The appearance of decagons, like that shown in figure 1, has led us to the conclusion that such monolayer films can be treated as an example of a two-dimensional quasicrystal of decagonal ordering [17]. Shortly after our paper [16] was published we realized, however, that this ordered phase is periodic. This was also pointed out by Schmiedeberg and Stark in their comments [18] on our work.…”
Section: Introductionmentioning
confidence: 93%
“…The results of Monte Carlo simulation reported in our recent works [15,16] have demonstrated that monolayer films formed on a square lattice of sites can order into a rather exotic phase in which every adatom has five nearest neighbors (see figure 1). The appearance of decagons, like that shown in figure 1, has led us to the conclusion that such monolayer films can be treated as an example of a two-dimensional quasicrystal of decagonal ordering [17].…”
Section: Introductionmentioning
confidence: 97%
“…Phase transitions induced by substrates are widely studied, for example on substrates with a one dimensional commensurate structure [2], which enhances the triangular order that is present without substrate. On other substrates with more complex periodic or even aperiodic symmetry, new phases have been observed [3][4][5][6][7][8][9][10][11]. For small interactions between the particles and the substrate, the phase preferred by the particles in the absence of a substrate strength prevails, while the phase preferred by the substrate is enforced for a strong substrate strength.…”
mentioning
confidence: 99%
“…For small interactions between the particles and the substrate, the phase preferred by the particles in the absence of a substrate strength prevails, while the phase preferred by the substrate is enforced for a strong substrate strength. In many systems, additional phases at intermediate substrate strength have been observed, for example for nanoparticles or micron-sized colloids [3,6,9,10], for vortices in type-II superconductors [12,13], for adsorbed atoms (cf., e.g., [7,14,15]) or molecules (for a recent review, see [16]). An intermediate phase also has been predicted from defect-mediated melting theory [17].…”
mentioning
confidence: 99%